2015
DOI: 10.1016/j.molcel.2015.05.008
|View full text |Cite
|
Sign up to set email alerts
|

The Cancer Cell Map Initiative: Defining the Hallmark Networks of Cancer

Abstract: Progress in DNA sequencing has revealed the startling complexity of cancer genomes, which typically carry thousands of somatic mutations. However, it remains unclear which are the key driver mutations or dependencies in a given cancer and how these influence pathogenesis and response to therapy. Although tumors of similar types and clinical outcomes can have patterns of mutations that are strikingly different, it is becoming apparent that these mutations recurrently hijack the same hallmark molecular pathways … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
92
1

Year Published

2016
2016
2019
2019

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 123 publications
(93 citation statements)
references
References 120 publications
0
92
1
Order By: Relevance
“…This contrasts with the results of studies described in recent publications about the reliability of the data associated with two very large cancer cell line screens pursued by different groups at different sites [5, 6, 8, 9]. We also observed that the main source of variation in our study could be attributed to the drugs used–further indicating that in certain settings, HTS data may indeed be reliable.…”
Section: Discussioncontrasting
confidence: 99%
“…This contrasts with the results of studies described in recent publications about the reliability of the data associated with two very large cancer cell line screens pursued by different groups at different sites [5, 6, 8, 9]. We also observed that the main source of variation in our study could be attributed to the drugs used–further indicating that in certain settings, HTS data may indeed be reliable.…”
Section: Discussioncontrasting
confidence: 99%
“…Reactome FI (RFI), a Cytoscape (Shannon et al . 2003) plugin app, combines gene ontology and biological pathways curated from online sources including CellMap (Krogan et al . 2015), Reactome (Milacic et al .…”
Section: Discussionmentioning
confidence: 99%
“…SignaLink v 2.0 (Fazekas et al, 2013) was mined to identify regulatory interactions of transcriptional, post-transcriptional and pathway regulators. Additional interactions present in non-disease conditions were identified from the Cancer Cell Map (Krogan et al, 2015), and the BioGRID database (Chatr-Aryamontri et al, 2015) was mined to identify unique interactions not reported by the other resources used. In addition to PPI databases and resources, primary literature was explored to identify experimentally verified interacting proteins in the human proteome.…”
Section: Methodsmentioning
confidence: 99%